FINANCIAL DISTRESS ANALYSIS USING ALTMAN Z-SCORE AND ZMIJEWSKI MODELS: CASE STUDY OF PT CHANDRA ASRI PACIFIC TBK (2019-2023) - Alif Pipin Kharisma; Nurul Qomari; Ruchan Sanusi; Dien Ajeng Fauziah (Jurnal Ekonomi Dan Bisnis, 2025)
This study aims to analyze the potential financial distress of PT Chandra Asri Pasific Tbk during the 2019-2023 period using two bankruptcy prediction models, namely Altman Z-Score and Zmijewski. The research method used in this research is descriptive qualitative method, this type of research data uses secondary data. Secondary data, obtained from the company's financial statements on the IDX web. The result of this study is that the value of the average EBIT and ROA indicators in 2019-2023 is quite low, namely 0.3%. However, overall the results of the altman Z-score model are said to be non-distress because it has a value greater than 2.6 (Z-Score>2.6) and in the Zmijewski model the company is also said to be not bankrupt because the value is less than 0 (X-Score<0). The conclusion of this study is that although the finances of PT Chandra Asri Pasific Tbk fluctuate, the company is still able to manage financial performance and manage risks.